Congenital hypothyroidism, the first cause of preventable mental retardation: a challenge for preventive medicine (2016)
ABSTRACT Congenital hypothyroidism is the most common endocrine disease in newborns and can be clinical or subclinical. It is the leading cause of treatable mental retardation and its prognosis is in the early screening and timely initiation of treatment; this is the reason why in Colombia the implementation of a neonatal screening with appropriate national coverage technique, comparable to those in other countries, is considered necessary. The aim of this article is to review and analyse the literature on congenital hypothyroidism focused on the definition, epidemiology, etiological factors, screening, diagnosis and treatment; by search in PubMed, EMBASE, REDALYC, OVID, MEDLINE, and CLINICAL KEY Dynamed data (access: May 2015). Besides reviewing the reports of the National Institute of Health in 2013 and 2014, the European guidelines for pediatric endocrinology society of 2014, Mexico’s 2008 guide neonatal congenital hypothyroidism and Colombian consensus for the diagnosis and management of thyroid diseases. MÉD UIS. 2016;29(1):53-60.Keywords: Congenital hypothyroidism. Neonatal screening. Epidemiology.